New insights on the bursting formation of star clusters in the large magellanic cloud - Piatti, Andres Eduardo (2011)
We present the results on the age estimates of 36 Large Magellanic Cloud (LMC) clusters obtained for the first time from CCD Washington CT1T2 photometry. By using the (T1, C − T1) and (T1, T1 − T2) diagrams, we estimated ages for the cluster sample using the δT1 index. We confirm that the studied cluster sample belong to the ∼2 Gyr bursting formation epoch of the LMC. Furthermore, when rebuiling the cluster age distribution – taken into account the estimated age errors – we found that the number of clusters with ages between 1 and 3 Gyr now doubles that of the known bursting cluster population, which suggests that the tidal interaction between both Magellanic Clouds and, perhaps, also the Milky Way, was more stronger than expected.